Dying to survive: Ransom piracy and ontologies of death in Coastal Somalia - Gilmer, Brittany (International review of victimology, 2024)
Interactions between long-term hostages and hostage takers remain undertheorized in criminology, and the present study attempts to fill this gap by utilizing testimonials from long-term hostages held aboard ships. We argue that seafarer hostages’ testimonials depict hijacked vessels as carceral sites that reflect and reproduce the global economic inequalities and racialized patterns of violence undergirding the broader geopolitics of piracy. Utilizing a threefold theoretical framework that unites and builds upon narrative inquiry, narrative criminology and victimology, and thanatopolitics, our analytical energies focus on the centrality of ontologies of death in hostages’ accounts of being held for ransom aboard ships. Our findings emphasize how ontologies of death evident in ransom piracy hostages’ accounts represent the hostage experience as encompassing different states of death, with hostages describing death as a real and ever-present threat that variously encompasses a psychological state of survival, a dehumanizing force, and a disciplinary tactic.